SYNTHESIS OF NEW THIAZOLIUM BETAINES AND THE RING EXPANSION REACTION VIA 1,4-DIPOLAR CYCLOADDITION - KIM, DC; KIM, DJ; PARK, SW; YOO, KH (HETERO CORPORATION, 1995)
The 1,4-dipolar cycloaddition of 3-phenyl-7-[N-phenyl(carbamoyl)]-5,6-dihydroimidazo[2,1-b]thiazolium betaine (7d) with a series of aliphatic alkylating agents such as ethyl bromoacetate, alpha-chloroacetone, and ethyl 4-chloroacetoacetate gave a variety of new ring-expanded cycloadducts 10a-c instead of ring transformation compounds 9. This result was derived from the difference of reactivity between N- and S-alkylations of thiazolium betaines 7a,d. The advantage of our method is to prepare the triheterocyclic compounds 10a-c of complicated structure using reactive thiazolium betaine 7d in a one-pot without isolation of intermediates. Treatment of N-bridged thiazolo compounds 1a-c with benzoyl isothiocyanate led to new thiazolium betaines 2a-c, which were reacted with methyl iodide to afford the S-alkylated quarternary ammonium salts 3a-c. Synthesis of new 2-iminothiazolinium betaines 5a,b also was carried out.
Keywords: IMIDAZOLE